2016
DOI: 10.1371/journal.pone.0151653
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Acute Exercise and Exercise Training on Plasma Homocysteine: A Meta-Analysis

Abstract: BackgroundAlthough studies have demonstrated that physical exercise alters homocysteine levels in the blood, meta-analyses of the effects of acute exercise and exercise training on homocysteine blood concentration have not been performed, especially regarding the duration and intensity of exercise, which could affect homocysteine levels differently.ObjectiveThe aim of this meta-analysis was to ascertain the effects of acute exercise and exercise training on homocysteine levels in the blood.MethodA review was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 68 publications
5
43
0
Order By: Relevance
“…The increase of Hcy levels after competition was somehow expected given the abundance of studies reporting the effects of exercise volume and intensity on plasma Hcy levels [10,21]. Konig and colleagues [21] showed that exercise-induced increase in the Hcy levels was dependent on baseline levels of training volume.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The increase of Hcy levels after competition was somehow expected given the abundance of studies reporting the effects of exercise volume and intensity on plasma Hcy levels [10,21]. Konig and colleagues [21] showed that exercise-induced increase in the Hcy levels was dependent on baseline levels of training volume.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies showed a higher incidence of HHcy in elite athletes compared with sedentary subjects, likely due to an increased consumption of SAM required for creatine synthesis during strenuous exercise, and creatine phosphate, as well as increased protein turnover [3,10,26]. Hcy increases in elite athletes may represent a relevant health issue, given the reported key role for HHcy as a contributor to early and advanced stages of CVD [6,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study from Iran (Alomari et al, 2016) and from China (Zhang et al, 2010;Kim et al, 2016) also demonstrated physical activity lowers the blood homocysteine concentration with vitamin supplements but in elders it lowers the homocysteine concentration without vitamin supplements. A European study suggested only trained aerobics lowers the blood homocysteine concentration (James & Earl, 2010;Deminice et al, 2016). A study (Buckner et al, 20016) demonstrated that activities Single and combined associations of accelerometer-assessed physical activity and muscle-strengthening activities associated with low concentration of homocysteine in blood.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, weightlifting exercise, which is well known to elicit one of the highest peak power outputs and to requires high metabolic cost [38][39][40][41], was suggested to be the best exercise modality to test the efficacy of POM as an ergogenic and recovery aid supplementation during intensive exercise [10]. Maximal strength-speed exercise is also a powerful stimulus to acutely increase concentrations of circulating [T], [C] and homocysteine [Hcy] [42][43][44]. There is some evidence that antioxidant beverages rich in polyphenols can attenuate [Hcy] levels in Alzheimer disease patients [45] and modulate endocrine responses in favor of an anabolic environment in healthy [19] and diseased [46] individuals.…”
Section: Introductionmentioning
confidence: 99%